Animal traction for agricultural development - Starkey, P.H.; Faye, A. (Technical Centre for Agricultural and Rural Cooperation, 1990)
Presents, in the first part, a summary of the activities, conclusions and evaluation of the third workshop of the West Africa Animal Traction Network (in both English and French). In the second part, there are edited papers prepared for the workshop, 30 papers in English and 29 in French with abstracts in both languages. The papers are grouped in terms of West African overviews, economic issues, implement development and country experiences. Papers discuss the impact of animal traction, and the constraints, in Senegal, The Gambia, Sierra Leone, Togo, Zambia, Kenya and Tanzania. Other papers discuss animal traction experiences in Morocco, Benin, Guinea, Ghana, Brazil and India.